Cervical cancer screening: comparative study of human papillomavirus detection between cervical cytology and urine samples - Jinwei Song; Jiandong Wang (BMC Women's Health)
Abstract Objective To evaluate the efficacy of urine-based human papillomavirus detection in detecting high-grade cervical lesions (CIN2+) compared to cervical cytology examination. Method The data of 458 patients with cytological abnormalities and/or positive human papillomavirus test results were retrospectively selected from December 1, 2017, to March 31, 2022, at the Beijing Obstetrics and Gynecology Hospital affiliated with Capital Medical University. Cervical cytology and urine samples were used to detect human papillomavirus status and analyze the correlation between the results and cervical biopsy results. Results Among the selected 458 samples, 386 were positive for human papillomavirus through cervical cytology examination, with a detection rate of 84.3%. Out of 458 urine samples, 362 were positive, with a detection rate of 79.0%. The data shows a high consistency between cervical cytology and urine sample testing, with a kappa value of 0.637 (P < 0.01). The most prevalent subtypes in cervical samples included HPV16, HPV58, and HPV52, while the detection rates of HPV16 and HPV58 subtypes were relatively high in urine samples. The comparison of subtype distribution between cervical and urine samples showed that the positivity rate of HPV44 subtype was consistent, both at 3.9%. Among the five HPV subtypes corresponding to the HPV nine-valent vaccine, the kappa value of HPV16 in cervical and urine samples was 0.791 (P < 0.05), the kappa value of HPV52 was 0.766 (P < 0.05), HPV18 was 0.762 (P < 0.05), HPV33 was 0.539 (P < 0.01), and HPV31 was 0.458 (P < 0.05). Among 458 specimens, the sensitivity of human papillomavirus detection in cervical cytology was 96.7%, with a specificity of 20.2% (P < 0.01). The sensitivity of human papillomavirus detection in urine samples was 85.2%, with a specificity of 23.2% (P < 0.01). Conclusion Urine human papillomavirus testing, as a non-invasive screening method, has significant application effects. The screening results are highly consistent with cervical cytology screening and may improve the compliance of women who do not want to undergo invasive gynecological examinations. This screening method simplifies the screening process and has great potential in screening cancer lesions and preventing cervical cancer.